Akkermansia muciniphila and osteoporosis: emerging role of gut microbiota in skeletal homeostasis - Gong, Yanlong; Ma, Xin; Huang, Jiumei; Zhang, Pengwei; Hai, Yunxiang; Song, Yongjia; Song, Min; Li, Yuanzhen; Wen, Haonan; Dong, Wantao (Frontiers in Microbiology, 2025)
Osteoporosis (OP) is a prevalent age-related skeletal disease. It is marked by compromised bone strength and higher fracture risk. Emerging evidence ties gut dysbiosis to OP development. Yet, the exact role of specific commensal bacteria remains unclear. Here, we review how Akkermansia muciniphila (A. muciniphila) affects bone metabolism. This mucin-degrading bacterium acts through three well-documented mechanisms: metabolite signaling, immune modulation, and gut-bone axis crosstalk. We also discuss emerging factors, such as host metabolic status, mechanical loading, and biomaterial applications. First, A. muciniphila produces short-chain fatty acids (SCFAs: acetate, propionate, butyrate), bile-acid metabolites, and vitamin K2. These substances boost Runx2-mediated osteoblast (OB) differentiation. They also suppress NF-κB-driven osteoclastogenesis. Second, the bacterium restores gut immune balance. It does so by expanding Foxp3+ regulatory T (Treg) cells and shifting macrophages toward an anti-inflammatory M2 phenotype. It also down-regulates IL-6, TNF-α, and RANKL signaling, thus limiting bone resorption. Third, via the gut-bone axis, A. muciniphila-derived extracellular vesicles (EVs) and miRNAs (e.g., miR-214-3p) enter the bloodstream. They strengthen intestinal barrier integrity, regulate calcium-phosphorus balance, and reduce systemic inflammation. Findings on A. muciniphila and bone health are conflicting. Some clinical and animal studies link higher abundance to better bone mass, with depletion worsening OP. Others, however, report negative correlations between A. muciniphila levels and bone mineral density (BMD) in separate cohorts. Most data come from pre-clinical models. Long-term human studies are scarce, and no clear causal links have been established. Future research should focus on randomized controlled trials. These trials need to define strain-specific effects, optimal doses, and safety profiles. The goal is to resolve these inconsistencies and turn A. muciniphila-based approaches into precise therapies for preventing and treating OP.